Stinging Nettles of Florida: Urtica - Wendy B. Zomlefer (EDIS)
Revised! HB002, a 4-page illustrated fact sheet by Wendy B. Zomlefer, describes this annual herb with stinging hairs, its classification, description, similar species, toxicity, and economic uses. Includes references. Published by the UF Herbarium, October 2008.